LPA receptor 1 mediates LPA-induced ovarian cancer metastasis: an in vitro and in vivo study. Issue 1 (December 2016) - Yu, Xuechen; Zhang, Yuanzhen; Chen, Huijun
Abstract Background The facts that LPA is present at high concentration in ovarian cancer patients' ascites and it may serve as a stimulator to cell migration, implicate the role of LPA in the ovarian cancer metastasis. Since LPA mediates various biological functions through its interaction with LPA receptors, we aim to investigate the correlation between the expression of LPA receptors and the metastasis of ovarian cancer. Methods To test whether the LPA responsiveness correlated with the metastatic capability of ovarian cancer cells, we performed LPA induced invasion assay and peritoneal metastatic colonization assay with a panel of established human ovarian cancer cell lines. The expression of LPAR1-3 in different ovarian cancer lines was examined by qRT-PCR. We also tested the effects of LPAR1 inhibition or overexpression on ovarian cancer cell's invasiveness. To confirm our laboratory results, we detected LPARs expression in specimens from 52 ovarian cancer patients by qRT-PCR and immunohistochemistry. Results Thirteen ovarian cancer cells were enrolled in the invasion assay. Ovarian cancer cell lines which responded well to LPA-induced invasion, also displayed good capability for metastatic colonization. On the contrary, cell lines with poor LPA responsiveness showed inferior metastatic potential in peritoneal colonization assay. High expression level of LPAR1 was detected in all of the metastatic ovarian cancer cell lines.T -test showed that LPAR1, not LPAR2 or LPAR3, expression was significantly higher in the metastatic cell lines than in the non-metastatic cell lines (P = 0.003). Furthermore, silencing LPAR1 alone could significantly reduce LPA-induced invasion (P < 0.001). Finally, we analyzed the correlation between the LPARs expression and clinicopathological features of the clinical cases. It indicated that LPAR1 expression rate increased significantly along with the more advanced stages (stage I: 16.67 %; II 50.00 %; III: 75.00 %; and IV: 100.00 %;P = 0.003). Besides that, LPAR1 expression was detected in all the 13 cases with abdominal metastasis more than 2 cm, 10 cases with retroperitoneal lymph node metastasis and 6 cases with hepatic metastasis. Moreover, the expression rate of LPAR2 significantly increased in ovarian cancer than in normal specimens (P = 0.039). LPAR3 expression showed the same trend as LPAR2, though the difference is not statistically significant (P = 0.275). Besides that LPAR2 and LPAR3 expression increased along with poorer differentiation (P = 0.002, P = 0.034, respectively). Conclusions Metastatic capability of ovarian cancer cells correlated well with their responsiveness to LPA for cell invasion. LPAR1 acts as the main mediator responsible for LPA-stimulated ovarian cancer cell invasion. LPAR2 and LPAR3 might play an role in carcinogenesis of ovarian cancer.